Self-Actualization Depicted in Paulo Coelho’s Eleven Minutes and Milena Busquets’s This Too Shall Pass - Errita Errita; Martha Pardede; Diah Rahayu Pratama (English Education Department, 2022)
This research of comparative literature compares two pieces of literature with a similar theme—Self-Actualization—from two distinct countries. By utilizing Abraham Maslow's Hierarchy of Needs theory, this study aimed to understand how the main characters are going about obtaining Self-Actualization. Maria and Blanca, the two main protagonists in the two literary works, are both undergoing the Self-Actualization process. Using the descriptive qualitative method, the author completes the analysis by presenting all of the data in the form of words and sentences. The writer collects data from various sources including Eleven Minutes by Paulo Coelho, This Too Shall Pass by Milena Busquets, and relevant books, articles, and journals to support the analysis. Based on the results of the analysis, the two literary works show similarities and differences relating to the Self-Actualization that is experienced by the two main characters of both literary works. Both main characters fulfilled four lower-level needs in the Hierarchy of Needs which are: Physiological needs, safety needs, love, and belonging needs, and esteem needs before finally achieving Self-Actualization.